Slip transmutation between basal 〈a〉 dislocation and {112¯1} twinning across {112¯4} twin boundary in titanium. (December 2022) - Liu, Xingxing; Yin, Xunlu; Yang, Xiaofeng; Chen, Hao; Wang, Jian
Graphical abstract: Abstract: Molecular dynamics simulations reveal slip transmutation mechanisms between basal 〈 a 〉 dislocations and { 11 2 ¯ 1 } twinning in titanium. When a co-planar pileup of basal 〈 a 〉 dislocations approaches ( 11 2 ¯ 4 ) coherent twin boundary (CTB), the 1st dislocation transmutes into a four-layer ( 11 2 ¯ 1 ) twin in the ( 11 2 ¯ 4 ) twin, forming a ( 11 2 ¯ 4 ) − ( 11 2 ¯ 1 ) double twin, and the 2nd and 3rd dislocations climb along the ( 11 2 ¯ 4 ) CTB and then transmute into twinning dislocations, thickening the ( 11 2 ¯ 1 ) secondary twin. When the ( 11 2 ¯ 1 ) secondary twin propagates and encounters the other ( 11 2 ¯ 4 ) CTB, a reverse transmutation happens associated with the nucleation and emission of partial dislocations.